A elaboração de propostas educacionais no ensino-aprendizagem de fisica: possibilidades e desafios para a formação de professores. - Sutil, Noemi (2006)
The aim of this work is to discuss some possibilities and challenges to Physics teachers' education with the developing of educational proposals. The educational proposal is presented as negotiated work, in a process of concepts and practices problem-posing with educational action research in an emancipatory way, in the basis of educational critical theory; the epistemological and socioIogiml aspects, which are negotiated in the educationa1 proposal developing, are specified and analyzed. The research was developed in the fourth and fifth degrees of Physics teachers' education, in Methodology and Practice of Physics I and li, 2004 and 2005, at Universidade Estadual de Ponta Grossa - PR. The conception of research utilized is the educational action research in an emancipatory way; the precepts of ethnography approach were fotlowed to collect and analyze data. Data were collected by direct observation: written data in a 'field diary", following a route, and audio records; the written works, made by graduation students, has been also utilized in data analysis. Data anaiysis has been realized according to a route and utilizing the analysis of the negotiations between epistemological and sociological aspects. The discussed possibilities are the utilization of the analysis of negotiations as a tool to propose interpretations and the developing of a conception of science in construction. The principals challenges presented are the efíecting of collective and collaborative work in the leaming and teaching process, the necessity of structures in medium and graduation leve1 to the developing of educationat proposals and the passage of an ingenuous perception to a critica[ perception as result of an adequate discussion of Physical knowledge.